Impact of Different Regimes in Treatment of Diabetic Ketoacidosis and Outcome of Liver Function Test (Medical Forum Monthly, 2023)
Objective: Comparing the impact of different regimes in treating diabetic ketoacidosis and evaluating the liver function testStudy Design: Experimental studyPlace and Duration of Study: This study was conducted at the Emergency Department of Ziauddin hospital Karachi from December 2022 to May 2023.Materials and Methods: 128 patients with confirmed diagnosis were selected for the study and divided into two groups each containing 64 patients each. In Group A, the interventional group patients were treated with both basal insulin and intravenous insulin infusion, while Group B, was only treated with intravenous infusion of insulin. Data was collected from all the patients which analyzed using SPSS version 22 and the p-value of less than 0.05 was set to be significant.Results: The mean age of these patients was 32.2±9.9 years ranging from 18 to 50 years. There were 69 (54%) male patients and 59 (46%) females. The median duration of resolution of DKA was 3.2 hours/day in group A and 3.8 hours/day in group B with a non-significant p-value of 0.068. Resolution in DKA was seen in 56% of cases in Group A and only in 47% of cases in Group B. The bilirubin test showed a statistically significant result with a p-value of <0.001 as the increased median value was noted in group A as compared with group B 1.5 mg/dL and 1.1 mg/dL respectively. Other values of liver function test such as ALT and ALP were not significantly altered.Conclusion: This study shows that the safe and efficient therapy of DKA may involve the addition of basal insulin (glargine) to intravenous insulin infusion. Remarkable effective in the treatment of DKA as compared to other therapeutic infusion, while there were no significant impact on liver function test.